The Teaching Vocabulary Through Students' Visual Spatial Intelligence - Norzulya Aries; Mujahidah; Nanning (Institut Agama Islam Negeri Parepare, 2020)
ABSTRACT Norzulya Aries,2020.Teaching Vocabulary Through Students’ Visual Spatial Intelligence at The Second year of MAN SidenrengRappang( Supervised by Hj. Nanning and Mujahidah). This research was aimed to investigate the teaching vocabulary through students’ visual spatial intelligence at the second year of MAN SidenrengRappang. The purpose of this research was to know is teaching vocabulary through students’ visual spatial intelligence able to enhance students’ vocabulary and are students interested in learning vocabulary through students’ visual spatial intelligence. This research took the second year focus on IX Mia 3 with 27 students as sample of MAN SidenrengRappang. This research was classified as quantitative research, where the instrument this research were test consist pre-test and post-test and questionnaire. The sampling technique of this research was random group sampling. In this research used pre-experimental design with one group pre-test and post-test The researcher found that: 1) teaching vocabulary through students’ visual spatial intelligence able to enhance students’ vocabulary. The students mean score of post-test more higher than pre-test, where the mean score of pre test 77,48 while the mean score of post test 83,70. Then the result of t-test was 3,76 was higher than value of t-table 1,706 and for the level significant 5% or 0.05 and degree of freedom (df) =26. Thus, the researcher concluded that teaching vocabulary through students’ visual spatial intelligence able to enhance students’ vocabulary. Furthermore, the nullhypothesis is rejected and the alternative hypothesis is accepted. 2) the students’ interested through the questionnaire also had concluded and most of them got 81-100 score with percentage was 83,76%. Based on the liker scale the student is very interested in learning vocabulary through students’ visual spatial intelligence. in concluded that teaching vocabulary thriugh students’ visual spatial intelligence able to enhance students’ vocabulary.